Confabulating, Misremembering, Relearning: The Simulation Theory of Memory and Unsuccessful Remembering - Michaelian, Kourken (Frontiers in Psychology, 2016)
This articles develops a taxonomy of memory errors in terms of three conditions: the accuracy of the memory representation, the reliability of the memory process, and the internality (with respect to the remembering subject) of that process. Unlike previous taxonomies, which appeal to retention of information rather than reliability or internality, this taxonomy can accommodate not only misremembering (e.g., the DRM effect), falsidical confabulation, and veridical relearning but also veridical confabulation and falsidical relearning. Moreover, because it does not assume that successful remembering presupposes retention of information, the taxonomy is compatible with recent simulation theories of remembering.